Magnificent leadership transform uncertainty, transcend circumstance, claim the future - Levitt, Sarah (Human resource management and organizational behavior collection, 2018)
1. Passion married to a high tolerance for uncertainty: featured narrative / Ben Fountain, writer -- 2. The lens we look through: framing and reframing: featured narrative / Dan Michelson, CEO, Strata Decision Technology -- 3. Accepting what is to create what can be: featured narrative / Selma Ungar, 91-year-old widow -- 4. Magnificence is not a solo journey: finding someone to hold the vision: featured narrative / Tim Toterhi, founder, Plotline Leadership -- 5. Undaunted: stretching through fear: featured narrative / Carolyn Colvin, former Acting Commissioner, Social Security Administration -- 6. Focusing on success while remaining open to iteration: featured narrative / Tom O'Keefe, actor, Bedlam Theater Company -- 7. Questing for self-mastery: featured narrative / Logan Bennett, president of the Alberta Avalanche Rescue Dog Association, director of The Canadian Avalanche Rescue Dog Association, and Avalanche Forecaster/Assistant Supervisor of Snow Safety at Sunshine Village Ski Resort: featured narrative / Brad Wilson, president and CEO, Blue Cross Blue Shield of North Carolina -- 8. A connection to contribution: creating a footprint: featured narrative / Dana Born, co-director of the Center for Public Leadership at Harvard University's Kennedy School of Government, lecturer in public policy, retired brigadier general, USAF, and ninth dean of the USAF Academy: featured narrative / Glen Tullman, CEO, Livongo Health, and managing partner, 7 Wire Ventures -- 9. Creating your own magnificent leadership: practical application -- The three fuel lines of magnificent leadership -- About the author -- Index